Optimization of AI-Empowered Cross-Cultural Communication in the Hainan Free Trade Port - Qian, Kun (Journal of Global Economy, Business and Finance, 2026)
Breakthroughs in artificial intelligence (AI), especially in machine translation, intelligent subtitling, AI-generated content (AIGC), and computer vision, have provided more efficient and accurate solutions for cross-cultural communication. As a major pilot zone for China’s opening-up, the Hainan Free Trade Port urgently needs to use AI technologies to improve information transmission in government communication, cultural promotion, and smart governance. However, AI-enabled cross-cultural communication still faces challenges such as contextual misinterpretation, insufficient cultural adaptation, and inadequate data regulation, all of which affect the accuracy and effectiveness of communication. This study examines the application of AI in policy communication, cultural brand promotion, and smart city management. On the basis of case analysis, it proposes optimization pathways such as the construction of AI corpora, the improvement of intelligent translation, and data-visualization-based communication strategies. The findings indicate that AI-empowered cross-cultural communication has broad application prospects, but its technological adaptability still needs to be further enhanced so as to strengthen the influence of the Hainan Free Trade Port in the global communication system.